Ancient Epistolary Theory: a Brief Overview (Annual of the Faculty of Philosophy in Skopje, 2018)
This paper is a brief overview of ancient theoretical views on letters: how the term‘epistle’ (έπιστολή, epistula) was defined in ancient times, what was discussed in the theoryof letters, what recommendations comprised epistolary decorum and what types of letterswere defined in ancient handbooks of letter-writing. The purpose of the paper is to reconstructancient epistolary theory based on surviving evidence. Direct evidence of this theoryare the excursus on letters in the treatise Περὶ ἑρμηνείας by Demetrius, two postclassicalhandbooks of letter-writing (“Τύποι έπιστολικοί” and “Έπιστολιμαῖοι χα-ρακτῆρες”), a brief tractate on letters written by the sophist Philostratus of Lemnos, oneepistle by Gregory of Nazinanzus and the appendix “De epistulis” at the end of the rhetoricalhandbook by Gaius Julius Victor “Ars rhetorica”. Indirect evidence, on the other hand, of ancientepistolary theory are the not-so-numerous incidental references to letters and letterwritingthat are mainly found in Cicero’s correspondence.
Keywords: ANCIENT EPISTOLARY THEORY; ANCIENT LETTER; EPISTOLARY DECORUM